Clinical impact of aortic valve replacement in patients with moderate mixed aortic valve disease - Onishi, Hirokazu; Izumo, Masaki; Ouchi, Toru; Yuki, Haruhito; Naganuma, Toru; Nakao, Tatsuya; Nakamura, Sunao (Frontiers in Cardiovascular Medicine, 2023)
Background Information is scarce regarding the clinical implications of aortic valve replacement (AVR) for patients suffering from moderate mixed aortic valve disease (MAVD), characterized by a combination of moderate aortic stenosis (AS) and regurgitation (AR). The objective of this retrospective study was to explore the clinical effects of AVR in individuals with moderate MAVD. Methods We examined the clinical data from patients with moderate MAVD and preserved left ventricular ejection fraction, who had undergone echocardiography in the period spanning from 2010 to 2018. Moderate AS was defined as aortic valve area index of 0.60–0.85 cm2/m2 and peak velocity of 3.0–4.0 m/s. Moderate AR was defined as a vena contracta width of 3.0–6.0 mm. The primary endpoint was a composite of all-cause death and heart failure hospitalization. Results Among 88 patients (mean age, 74.4 ± 6.8 years; 48.9%, men), 44 (50.0%) required AVR during a median follow-up period of 3.3 years (interquartile range, 0.5–4.9). Mean values of specific aortic valve variables are as follows: aortic valve area index, 0.64 ± 0.04 cm2/m2; peak velocity, 3.40 ± 0.30 m/s; and vena contracta width, 4.1 ± 0.7 mm. The primary endpoint occurred in 32 (36.4%) patients during a median follow-up duration of 5.3 years (interquartile range, 3.2–8.0). Multivariable analysis revealed that AVR was significantly associated with the endpoint (hazard ratio, 0.248; 95% confidence interval, 0.107–0.579; p = 0.001) after adjusting for age, B-type natriuretic peptide, and the Charlson comorbidity index. Patients who underwent AVR during follow-up had significantly lower incidence rates of the endpoint than those managed with medical treatment (10.2% vs. 44.1% at 5 years; p < 0.001). Conclusions Approximately half of the patients diagnosed with moderate MAVD eventually necessitated AVR throughout the period of observation, leading to positive clinical results. Vigilant tracking of these patients and watchful monitoring for signs requiring AVR during this time frame are essential.